Current state of lobster exports in Brazil (Research, Society and Development, 2020)
The present study aims to bring updated information about the export of lobsters in Brazil, mapping products, quantities, origins and destinations of exports of this crustacean, from its industrialization to the country where it will be consumed. Lobster is the main fisheries product export from Brazil, representing 30% of the total shipped abroad. From the analysis of quantitative data and exploratory statistics, exports of lobster products reached 6,054 tons and 92.46 million dollars in 2019. Frozen tails are prevalent, with 4,625 t. (76.40%) and 64.2 million dollars (69.47%). The whole frozen lobsters appear as the second most exported product, with 1,273 tons. (21.04%) and 24.6 million dollars (26.59%) in 2019. Despite the incipient, it deserves to be highlighted the crescent evolution in the export volume of live / fresh lobsters, with 155 ton. in 2019 and 3.65 million dollars (3.94%). Ceará state is traditionally and historically the largest lobster exporter in Brazil, with 3,881 t. in 2019 (64.11% of the total). The main destination of the Brazilian lobsters continues to be the United States, which imported 67.10% of all Brazilian lobster, with a negotiated volume of more than 4 thousand tons. China appears as the second largest destination for exports of Brazilian lobsters, with 880 thousand tons, followed by Australia with 466 thousand tons.